1992
DOI: 10.1128/jvi.66.2.1119-1128.1992
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of adeno-associated virus Rep78, Rep52, and Rep40 and their biochemical characterization

Abstract: We have used differential cell extraction and conventional chromatography to separate and partially purify the four adeno-associated virus (AAV) nonstructural proteins Rep78, Rep68, Rep52, and Rep4O. In the cytoplasmic extracts Rep52 and Rep4O were present in greater abundance than Rep68 and Rep78, with Rep78 being the least abundant. In nuclear extracts the four Rep proteins were approximately equal in abundance. Regardless of the subcellular fraction examined, three of the Rep proteins (Rep78, Rep68, and Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
126
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(137 citation statements)
references
References 45 publications
11
126
0
Order By: Relevance
“…AAV protein expression was analyzed by Western blotting. All four types of Rep protein were detected, and Rep78 appeared as a doublet as described previously (12). The additional bands migrating below Rep40 and of about 55 kilodaltons (kD) were detected, but the origins of these products are unknown.…”
Section: Rep and Cap Expression Patterns With Various Helper Plasmidssupporting
confidence: 57%
“…AAV protein expression was analyzed by Western blotting. All four types of Rep protein were detected, and Rep78 appeared as a doublet as described previously (12). The additional bands migrating below Rep40 and of about 55 kilodaltons (kD) were detected, but the origins of these products are unknown.…”
Section: Rep and Cap Expression Patterns With Various Helper Plasmidssupporting
confidence: 57%
“…Completion of the replication scheme requires resolution of the covalently closed hairpin structure by Repdependent nicking, which results in the transfer of this sequence to the progeny DNA. The nicking reaction generates a new 3Ј OH on the parental strand, providing the substrate for copying back the transferred ITR sequences (13,15 for a review, see reference 22).…”
mentioning
confidence: 99%
“…Genetic analysis of the AAV genome has demonstrated that the p5 Rep proteins (Rep78 and Rep68) are required to reg-ulate transcription from all three promoters and to replicate the viral DNA (20,53). Several biochemical properties have been characterized for the p5 Rep proteins during replication; these include site-specific endonuclease (24,51), DNA helicase (24,58), and DNA binding (24,25,38) activities. In the absence of Ad, Rep has been shown to repress both p5 and p19 transcription (21,30).…”
mentioning
confidence: 99%